Metallic nanoparticles-decorated NdxY1-xAl3(BO3)4 sub-micrometric particles to enhance anti-Stokes excitation performance - Eloísa G. Hilário; Tatiana Habib; Célio V.T. Maciel; Rodrigo F. da Silva; Daniel F. Luz; Gabriela S. Soares; Bruno Caillier; Carlos Jacinto; Lauro J.Q. Maia; José Maurício A. Caiut; André L. Moura (Optical Materials: X, 2023)
In the anti-Stokes excitation of trivalent rare-earth ions (RE3+), the excitation photons energy is smaller than that of a given absorption transition, and the energy mismatch can be compensated by phonons annihilation from the host lattice. Since the phonon occupation number increases with temperature, heating the system generally increases the efficiency of anti-Stokes excitation. Here, we exploited the intrinsic heating associated with light-to-heat conversion in the interaction of excitation laser light with metallic nanoparticles (Ag or Au) on the surface of submicrometric particles of NdxY1.00-xAl3(BO3)4 (x = 0.10, 0.20, and 1.00) in order to enhance the efficiency of the anti-Stokes excitation at 1064 nm. Several upconversion emissions are observed from 600 nm to 880 nm, the most intense being at 750 nm due to the Nd3+ transition {4F7/2, 4S3/2} → 4I9/2. Giant enhancements are demonstrated, when compared to undecorated NdxY1.00-xAl3(BO3)4 particles. The present results can be expanded to other luminescent materials as well as excitation wavelengths.